piRNA Production Requires Heterochromatin Formation in Drosophila - Rangan, Prashanth; Malone, Colin D.; Navarro, Caryn; Newbold, Sam P.; Hayes, Patrick S.; Sachidanandam, Ravi; Hannon, Gregory J.; Lehmann, Ruth (Current biology, 2011)
Protecting the genome from transposable element (TE) mobilization is critical for germline development. In Drosophila, Piwi proteins and their bound small RNAs (piRNAs) provide a potent defense against TE activity. TE targeting piRNAs are processed from TE-dense heterochromatic loci termed piRNA clusters. Although piRNA biogenesis from cluster precursors is beginning to be understood, little is known about piRNA cluster transcriptional regulation. Here, we show that deposition of histone 3 lysine 9 by the methyltransferase dSETDB1 (egg) is required for piRNA cluster transcription. In the absence of dSETDB1, cluster precursor transcription collapses in germline and somatic gonadal cells and TEs are activated, resulting in germline loss and a block in germline stem cell differentiation. We propose that heterochromatin protects the germline by activating the piRNA pathway. [Display omitted] ► Germline stem cell differentiation requires H3K9 methyltransferase (SETDB1) ► piRNA clusters are targets of H3K9me3 in the gonad ► dSETDB1 regulates piRNA levels by controlling piRNA cluster transcription ► Transposon derepression is sufficient to block germline stem cell differentiation